Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1200/jco.2018.77.9124
|View full text |Cite
|
Sign up to set email alerts
|

Progression-Free Survival as a Surrogate End Point for Overall Survival in First-Line Diffuse Large B-Cell Lymphoma: An Individual Patient–Level Analysis of Multiple Randomized Trials (SEAL)

Abstract: Purpose Overall survival (OS) is the definitive and best-established primary efficacy end point to evaluate diffuse large B-cell lymphoma (DLBCL) therapies, but it requires prolonged follow-up. An earlier end point assessed post-treatment would expedite clinical trial conduct and accelerate patient access to effective new therapies. Our objective was to formally evaluate progression-free survival (PFS) and PFS at 24 months (PFS24) as surrogate end points for OS in first-line DLBCL. Patients and Methods Individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
54
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 53 publications
(17 reference statements)
2
54
0
1
Order By: Relevance
“…Furthermore, PFS is recognized by the FDA as a valid surrogate endpoint for non-Hodgkin lymphomas (https:// www.fda.gov/downloads/Drugs/DevelopmentApprovalProcess/ DevelopmentResources/UCM614369.xlsx). For DLBCL, a recent analysis of multiple randomized trials with a total sample size of 7507 patients also clearly supported the use of PFS, and showed that 2-year PFS significantly correlates with OS [20].…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, PFS is recognized by the FDA as a valid surrogate endpoint for non-Hodgkin lymphomas (https:// www.fda.gov/downloads/Drugs/DevelopmentApprovalProcess/ DevelopmentResources/UCM614369.xlsx). For DLBCL, a recent analysis of multiple randomized trials with a total sample size of 7507 patients also clearly supported the use of PFS, and showed that 2-year PFS significantly correlates with OS [20].…”
Section: Discussionmentioning
confidence: 92%
“…This issue is an important one to consider in other very large clinical data sets with direct ascertainment of the treatment regimen, dosing, timing of dose delivery, and outcomes. Large clinical data sets, such as the Surrogate Endpoints for Aggressive Lymphoma (SEAL) collaboration, now are becoming available to address such questions …”
Section: Discussionmentioning
confidence: 99%
“…Large clinical data sets, such as the Surrogate Endpoints for Aggressive Lymphoma (SEAL) collaboration, now are becoming available to address such questions. 55 In terms of methodology, even though the Aalen-Johansen estimator is the canonical nonparametric maximum likelihood estimator for multistate models with guaranteed asymptotical convergence, [17][18][19]21,29,56 caution must be exercised because the size of the available data gets smaller. This is unlikely to pose an issue for subpopulation analyses (eg, patients using R-CHOP) but might be a concern for individualized predictions because each covariate defining an individual patient also shrinks the size of the available data that the estimator uses.…”
Section: Discussionmentioning
confidence: 99%
“…For the survival analyses, the endpoints were progression-free survival (PFS) and overall survival (OS). 13 OS was counted from the date of diagnosis to the date of death from any cause. PFS was counted from the date of diagnosis to the date of lymphoma recurrence or death from any cause or the date of last follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…The associations between the MSI status and clinicopathologic features were analyzed by Pearson's chi‐square test, Mann‐Whitney test or the Fisher's exact test. For the survival analyses, the endpoints were progression‐free survival (PFS) and overall survival (OS) . OS was counted from the date of diagnosis to the date of death from any cause.…”
Section: Methodsmentioning
confidence: 99%